The Influence of Service Quality, User Experience and Promotion on Passenger Loyalty Mediated by Reuse Intention of Jaklingko Mikrotrans in Jakarta - Muhammad Gusti Guntara; Peppy Fachrial; Abdullah Ade Suryobuwono (DINASTI RESEARCH, 2026)
This study aims to analyze the effect of service quality, user experience, and promotion on passenger loyalty through reuse intention of Jaklingko Microtrans in East Jakarta. The research object was passengers of Jaklingko Microtrans operating on seven routes with departure and arrival points at Rawamangun Terminal. A quantitative approach was employed using a survey method with questionnaires distributed to 100 randomly selected respondents. Data were analyzed using Partial Least Square with SmartPLS software, supported by Importance Performance Analysis and Customer Satisfaction Index. The results indicate that promotion has a significant effect on reuse intention, while service quality and user experience do not. User experience and reuse intention significantly influence passenger loyalty, whereas service quality and promotion do not directly affect loyalty. Indirectly, promotion influences loyalty through reuse intention. The study concludes that strengthening promotional strategies and improving user experience are key factors in enhancing passenger loyalty toward Jaklingko Microtrans services.